APLIKASI TATA KELOLA BARANG INVENTARIS DI SDN SEMPU 2 KOTA SERANG BERBASIS WEB - Huswatun Hasanah; Rizki Fatullah; Mohamad Fahmi (Jurnal Sistem Informasi dan Informatika (Simika), 2022)
SDN Sempu 2 Kota Serang is an institution engaged in the field of education. The inventory of goods at the school has a problem, namely the large number of inventory items should be managed so that some items sometimes escape the attention of officers and make it difficult to supervise the process. This is because SDN Sempu 2 Kota Serang still uses notebooks in the inventory management process so that information about school inventory items is difficult to know with certainty and quickly. Inventory report recapitulation is also still being carried out by recording in notebooks and in a period that makes it impossible to obtain information in real time or if needed at any time. This study aims that the application developed can provide convenience in monitoring inventory items owned by SDN Sempu 2 Kota Serang and provide a real time and accurate recapitulation of reports. The research method applied in this research is the waterfall method. The conclusion obtained is that making the application can facilitate and manage item data when needed so that item data will not be lost again. In addition, report generation is easier and more efficient.